Mengembangkan Literasi Budaya melalui Permainan Ular Tangga: Sebuah Pendekatan Edukatif dan Menyenangkan - Purwati, Pipit; Wakhyudin, Husni; Nuruliarsih; Prima, Filia (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The snakes and ladders game, as a traditional board game, has great potential to be used as an educational tool in developing cultural literacy. Cultural literacy is the ability to understand, appreciate and interact with a variety of different cultures, which is becoming increasingly important in the current era of globalization. This research aims to explore how the snakes and ladders game can be modified and used to develop cultural literacy in fifth grade students at SDN Sambirejo 02. The methodology used is a qualitative approach with a descriptive research design. Data was collected through observation, interviews and data analysis during the implementation of activities. Data analysis was carried out descriptively to see changes in students' understanding and attitudes towards local culture after playing snakes and ladders. The research results show that the snakes and ladders game developed in this research is effective in increasing cultural literacy in elementary school students. Students who play this game show an increased understanding of regional culture in Indonesia, as well as a higher interest in studying Indonesian culture. Thus, integrating the traditional game snakes and ladders in learning can be an effective strategy in developing cultural literacy. The recommendation from this research is that educators consider the use of educational games in the curriculum to increase cultural literacy and build a fun learning environment.